2011
DOI: 10.1371/journal.pone.0016038
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitochondrial Calcium Sensitivity and Abnormal Expression of Innate Immunity Genes Precede Dopaminergic Defects in Pink1-Deficient Mice

Abstract: BackgroundPTEN-induced kinase 1 (PINK1) is linked to recessive Parkinsonism (EOPD). Pink1 deletion results in impaired dopamine (DA) release and decreased mitochondrial respiration in the striatum of mice. To reveal additional mechanisms of Pink1-related dopaminergic dysfunction, we studied Ca2+ vulnerability of purified brain mitochondria, DA levels and metabolism and whether signaling pathways implicated in Parkinson's disease (PD) display altered activity in the nigrostriatal system of Pink1−/− mice.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(138 citation statements)
references
References 142 publications
(194 reference statements)
5
132
1
Order By: Relevance
“…Additionally, Akundi et al showed repression of PINK1 expression results in heightened susceptibility to inflammatory response-mediated DA neuron loss. 115 Elevated striatal levels of IL-1, IL-10, and IL-12 were detected in PINK1 null mice following LPS treatment. Furthermore, embryonic fibroblasts derived from PINK1 knockout mice exhibited repressed NF-kB activity in response to an inflammatory environment suggesting that PINK1 deficient neurons might have increased susceptibility to inflammatory response-mediated death.…”
Section: Pink1 (Park6)mentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, Akundi et al showed repression of PINK1 expression results in heightened susceptibility to inflammatory response-mediated DA neuron loss. 115 Elevated striatal levels of IL-1, IL-10, and IL-12 were detected in PINK1 null mice following LPS treatment. Furthermore, embryonic fibroblasts derived from PINK1 knockout mice exhibited repressed NF-kB activity in response to an inflammatory environment suggesting that PINK1 deficient neurons might have increased susceptibility to inflammatory response-mediated death.…”
Section: Pink1 (Park6)mentioning
confidence: 96%
“…Furthermore, embryonic fibroblasts derived from PINK1 knockout mice exhibited repressed NF-kB activity in response to an inflammatory environment suggesting that PINK1 deficient neurons might have increased susceptibility to inflammatory response-mediated death. 115 …”
Section: Pink1 (Park6)mentioning
confidence: 99%
“…Subsequently, Parkin promotes the degradation of depolarized mitochondria through mitophagy [8,9,10]. Besides regulating mitochondrial quality control loss of PINK1 in mice directly compromises mitochondrial function [11,12,13], and PINK1 protects cells and mitochondria against oxidative stress [14,15]. We recently described PINK1 -/- mice that develop age-dependent loss of dopamine and showed that mitochondria from the brain of PINK1 -/- mice undergo increased calcium-induced permeability transition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Besides regulating mitochondrial quality control loss of PINK1 in mice directly compromises mitochondrial function [11,12,13], and PINK1 protects cells and mitochondria against oxidative stress [14,15]. We recently described PINK1 -/- mice that develop age-dependent loss of dopamine and showed that mitochondria from the brain of PINK1 -/- mice undergo increased calcium-induced permeability transition [12]. Here, we further characterized mitochondrial function, structure and adaptive changes in primary mouse embryonic fibroblasts (MEF) from PINK1-deficient (PINK1 -/- ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…29 Moderate microgliosis was reported in the only postmortem report on a brain of a PD patient with 2 PINK1 mutations. 30 Of note, several of the markedly upregulated genes in our gene expression analysis (see see Supplementary Table), such as complement factor H and calpain, are involved in immune mechanisms and activation of microglial cells.…”
Section: =2mentioning
confidence: 97%